Venetoclax with dose-adjusted EPOCH-R as initial therapy for patients with aggressive B-cell lymphoma: a single-arm, multicentre, phase 1 study. Issue 11 (November 2021) - Rutherford, Sarah C; Abramson, Jeremy S; Bartlett, Nancy L; Barta, Stefan K; Khan, Nadia; Joyce, Robin; Maddocks, Kami; Ali-Shaw, Trisha; Senese, Silvia; Yuan, Ying; Westin, Jason; Leonard, John P
Summary: Background: Dose-adjusted EPOCH-R (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab) is a front-line treatment for patients with aggressive B-cell lymphomas. Bcl-2 is associated with chemoresistance due to BCL2 gene rearrangement or protein overexpression and is antagonised by venetoclax. We aimed to assess the safety of venetoclax with dose-adjusted EPOCH-R as initial therapy in aggressive B-cell lymphoma. Methods: We conducted a single-arm, phase 1 study across seven treatment centres in the USA. Eligible patients were aged 18–80 years with histologically confirmed, previously untreated diffuse large B-cell lymphoma, transformed indolent non-Hodgkin lymphoma, high-grade B-cell lymphoma with double-hit or not otherwise specified, or primary mediastinal B-cell lymphoma, with Ann Arbor stage II–IV and Eastern Cooperative Oncology Group performance status of 0–2. Participants received six cycles of oral venetoclax 400 mg, 600 mg, or 800 mg once daily for 10 days per cycle with dose-adjusted EPOCH-R (one cycle every 3 weeks; baseline doses were intravenous rituximab 375 mg/m 2 on day 1, intravenous etoposide 50 mg/m 2 on days 1–4, oral prednisone 60 mg/m 2 twice daily on days 1–5, intravenous vincristine 0·4 mg/m 2 on days 1–4, intravenous cyclophosphamide 750 mg/m 2 on day 5, and intravenous doxorubicin 10 mg/m 2 on days 1–4). A subsequent cohort received venetoclax 600 mg once daily for 5 days per cycle. The primary endpoints were the maximum tolerated dose, dose-limiting toxicities, and the recommended phase 2 dose of venetoclax. Analyses were done per protocol. This trial is registered with ClinicalTrials.gov, NCT03036904, and enrolment is now closed. Findings: Between Feb 3, 2017, and June 4, 2019, 34 patients were assessed for eligibility, and 30 were enrolled and received venetoclax with dose-adjusted EPOCH-R. The median patient age was 64·0 years (IQR 51·6–69·4). The maximum tolerated dose was 800 mg for 10 days and the established recommended phase 2 dose was 600 mg for 5 days due to tolerability for treatment duration. One (3%) of 30 patients had a dose-limiting toxicity in cycle one (grade 4 thrombocytopenia with 800 mg dose). The most common grade 3–4 adverse events were cytopenias (28 [93%] of 30 patients); febrile neutropenia occurred in 19 (63%) patients. Grade 3–4 non-haematological adverse events included hypophosphataemia (n=10), hypokalaemia (n=7), and hyperglycaemia (n=5). Serious adverse events included infection (n=7) and gastrointestinal toxicities including abdominal pain (n=3), colonic perforation (n=1), and small intestinal obstruction (n=1). There was one treatment-related death (sepsis). Overall response rate was 96·7% (95% CI 82·8–99·9); 28 (93·3% [77·9–99·2]) of 30 patients had complete response and one (3·3% [0·1–17·2]) had a partial response. Interpretation: Venetoclax with dose-adjusted EPOCH-R showed an acceptable safety profile at the recommended phase 2 dose and had encouraging preliminary activity in this population at high risk of adverse outcomes, and is worthy of further study. The combination is being investigated in Alliance 051701 (NCT03984448 ). Funding: Genentech.